Phylogeography of Rattus norvegicus in the South Atlantic Ocean - Melanie Hingston; Sally Poncet; Ken Passfield; Michael Tabak; Sofia Gabriel; Stuart Piertney; James Russell (Diversity, 2016)
Norway rats are a globally distributed invasive species, which have colonized many islands around the world, including in the South Atlantic Ocean. We investigated the phylogeography of Norway rats across the South Atlantic Ocean and bordering continental countries. We identified haplotypes from 517 bp of the hypervariable region I of the mitochondrial D-loop and constructed a Bayesian consensus tree and median-joining network incorporating all other publicly available haplotypes via an alignment of 364 bp. Three Norway rat haplotypes are present across the islands of the South Atlantic Ocean, including multiple haplotypes separated by geographic barriers within island groups. All three haplotypes have been previously recorded from European countries. Our results support the hypothesis of rapid Norway rat colonization of South Atlantic Ocean islands by sea-faring European nations from multiple European ports of origin. This seems to have been the predominant pathway for repeated Norway rat invasions of islands, even within the same archipelago, rather than within-island dispersal across geographic barriers.